Lower perceived stress among physically active elite private university students with higher levels of gratitude - Kabiri, Laura S.; Le, Jennie; Diep, Cassandra S.; Chung, Eunbi; Wong, Jacob; Perkins-Ball, Amanda M.; Perkins, Heidi Y.; Rodriguez, Augusto X. (Frontiers in Sports and Active Living, 2024)
Elite private universities have high stress levels, particularly for underrepresented populations. While physical activity and gratitude can both reduce stress, independent effects from gratitude and interaction effects between physical activity and gratitude on stress are insufficiently explored. Our study investigated these effects among undergraduates at elite private universities. Undergraduates (n = 145) completed an online survey in Fall 2022. Moderate-high physical activity levels were reported by 96.19% of the sample. No significant interaction effect between physical activity and gratitude was seen nor a significant main effect of physical activity on perceived stress. A significant main effect of gratitude on perceived stress [F (2, 99) = 16.732, p < .001, ω2 = .253] was found with higher perceived stress among participants with low compared to moderate (p = .001) or high gratitude (p < .001). Gratitude exerted an independent, significant effect on perceived stress among elite university undergraduates and could be used as an additional healthy coping mechanism along with physical activity to combat stress.